PERAN MEDIASI STRES KERJA PADA PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN WANITA DIVISI PRODUKSI BOBBIN PT SCANDINAVIAN TOBACCO GROUP INDONESIA - Adinda Rahmawati Syarifuddin; Hesty Prima Rini (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze how the work environment affects the performance of female employees, both directly and indirectly through work stress as a mediating variable, in the yarn production division at PT Scandinavian Tobacco Group Indonesia. This study uses a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. The research population consisted of 554 female employees, with a total of 233 respondents selected through an online questionnaire distributed via Google Form. The study’s results indicate that the work environment has a significant positive impact on employee performance, and that the this impact is mediated by work stress, which positively influences performance. These results highlight that a supportive and comfortable work environment can help reduce stress levels and increase employee productivity in completing their tasks efficiently and on time.